Collaborative Chronic Disease Management in Primary and Emergency Care: A Multidisciplinary Approach Integrating Health Administration, Pharmacy, Nursing, General Practice, EMS, Psychology, and Laboratory Services - Alanazi, Abdulhafit Zuzua M; Abdulrahman, Moneerah Abdullah; Alsaiyegh, Badrayh Mohammed Hussain; Alabdullatif, Wadeah Ibrahim Ahmed; Buhelal, Rbab Hussin; Almutairi, Fahad Sahw; Alasmari, Ali Mohammed Abdullah; Alboti, Wejdan Abdullah; Al Qahtani, Majid Mohammed Qassim; Aldossari, Falah Manie Falah; Alnemari, Howaida Abdullah; Aljubran, Amal Hussain Mohammed (Journal of Ecohumanism, 2024)
Chronic diseases such as diabetes mellitus, cardiovascular diseases, chronic respiratory disorders, and mental health conditions have become the leading causes of death and disability worldwide, accounting for a vast proportion of healthcare utilization and expenditure. Managing these conditions effectively requires long-term, continuous, and comprehensive care that addresses not only the physiological aspects but also the psychosocial and behavioral dimensions of health. The traditional healthcare model, characterized by fragmentation and reactive responses, has proven insufficient for managing the complexity of chronic illnesses. This review article underscores the value of a multidisciplinary and integrated approach that bridges the gap between primary care and emergency services. It examines the roles of diverse healthcare professionals—health administrators, pharmacists, nurses, general practitioners, EMS personnel, psychologists, and laboratory technicians—in delivering coordinated and patient-centered care. Each profession contributes essential expertise, and when functioning cohesively, they form a network capable of providing proactive monitoring, timely interventions, psychosocial support, and data-driven decision-making. Furthermore, the article discusses real-world barriers to integration, such as institutional silos, lack of interoperable health information systems, role ambiguity, and inconsistent interprofessional education. Drawing from international case studies and evidence-based models, it offers practical recommendations to foster collaboration, including policy reforms, the use of shared care plans, interprofessional training programs, and digital integration strategies. In doing so, this review presents a compelling case for a systemic shift toward team-based chronic disease management across healthcare levels, aiming for improved clinical outcomes, enhanced patient experiences, and more sustainable healthcare systems.